KEWAJIBAN SINGGAH DI TERMINAL BAGI KENDARAAN BERMOTOR DALAM TRAYEK BUS ANTARKOTA (Studi Batulayang) - Sadewo, Restu; Nuryanti, Aktris; Ismawartati, Ismawartati (Faculty of Law, Universitas Tanjungpura, 2023)
AbstractThis research was conducted at the Pontianak City Transportation Service, the West Kalimantan Province Transportation Service, the Pontianak City Police, and the Batulayang Terminal. This study aims to identify and analyze the causes of public motorized vehicles on intercity bus routes within the province that do not stop at the Batulayang terminal, and how to control public motorized vehicles on intercity bus routes within the province that do not stop at the Batulayang terminal. This research was carried out using empirical legal research methods, with structured interviews and with an open system, how to obtain data by using direct interviews with informants, both the Pontianak City Transportation Service, the West Kalimantan Province Transportation Service, the Pontianak City Police, and at the Batulayang Terminal. Based on the results of the research and discussion, the following results are obtained: that many inter-city buses within the province do not stop at the Batulayang terminal. This is due to the fact that there is no combination between inter-city buses within the province and urban transportation. The absence of urban transportation has caused inter-provincial inter-city buses to be allowed to enter the city of Pontianak to deliver passengers directly to their destinations within the hours set by Pontianak Mayor Regulation No. 48 of 2016. AbstrakPenelitian ini dilakukan di Dinas Perhubungan Kota Pontianak, Dinas Perhubungan Provinsi Kalimantan Barat, Kepolisian Resor Kota Pontianak, dan Terminal Batulayang. Penelitian ini bertujuan untuk mengetahui dan menganalisis penyebab Kendaraan Bermotor Umum Dalam Trayek Bus Antarkota Dalam Provinsi yang tidak singgah di Terminal Batulayang, dan bagaimana pengawasan terhadap Kendaraan Bermotor Umum Dalam Trayek Bus Antarkota Dalam Provinsi yang tidak singgah di Terminal Batulayang. Adapun penelitian ini dilakukan dengan metode penelitian hukum empiris, dengan wawancara terstruktur serta dengan sistem terbuka, cara memperoleh data dengan mengunakan wawancara langsung kepada informan baik itu Dinas Perhubungan Kota Pontianak, Dinas Perhubungan Provinsi Kalimantan Barat, Kepolisian Resor Kota Pontianak, dan di Terminal Batulayang. Berdasarkan hasil penelitian dan pembahasan diperoleh hasil sebagai berikut: bahwa banyak Bus Antarkota Dalam Provinsi yang tidak singgah di Terminal Batulayang. Hal tersebut disebabkan memang tidak adanya perpaduan antara Bus Antarkota Dalam Provinsi dan Angkutan Perkotaan. Sudah tidakadanya Angkutan Perkotaan menyebabkan Bus Antarkota Dalam Provinsi diperbolehkan untuk memasuki Kota Pontianak untuk mengantarkan penumpang langsung ke tempat tujuan dengan batas jam yang telah ditentukan oleh Peraturan Wali Kota Pontianak Nomor 48 tahun 2016.